Taurine Stimulates Thermoregulatory Genes in Brown Fat Tissue and Muscle without an Influence on Inguinal White Fat Tissue in a High-Fat Diet-Induced Obese Mouse Model - Kyoung Soo Kim (Foods, 2020)
This study was conducted to investigate if taurine supplementation stimulates the induction of thermogenic genes in fat tissues and muscles and decipher the mechanism by which taurine exerts its anti-obesity effect in a mildly obese ICR (CD-1®) mouse model. Three groups of ICR mice were fed a normal chow diet, a high-fat diet (HFD), or HFD supplemented with 2% taurine in drinking water for 28 weeks. The expression profiles of various genes were analyzed by real time PCR in interscapular brown adipose tissue (BAT), inguinal white adipose tissue (iWAT), and the quadriceps muscles of the experimental groups. Genes that are known to regulate thermogenesis like PGC-1α, UCP-1, Cox7a1, Cox8b, CIDE-A, and β1-, β2-, and β3-adrenergic receptors (β-ARs) were found to be differentially expressed in the three tissues. These genes were expressed at a very low level in iWAT as compared to BAT and muscle. Whereas, HFD increased the expression of these genes. Taurine supplementation stimulated the expression of UCP-1, Cox7a1, and Cox8b in BAT and only Cox7a1 in muscle, while there was a decrease in iWAT. In contrast, fat deposition-related genes, monoamine oxidases (MAO)-A, and -B, and lipin-1, were decreased by taurine supplementation only in iWAT and not in BAT or muscle. In conclusion, the potential anti-obesity effects of taurine may be partly due to upregulated thermogenesis in BAT, energy metabolism of muscle, and downregulated fat deposition in iWAT.